Delineating the controlling mechanisms of arsenic release into groundwater and its associated health risks in the Southern Loess Plateau, China. (1st July 2022) - Zhang, Xiao; Zhao, Rong; Wu, Xiong; Mu, Wenping; Wu, Chu
Highlights: SOM identified the nonlinear relationship between As and physicochemical parameters. Desorption of As-bearing Fe (hydro)oxide minerals possibly controls As mobilization. Evaporites weathering may be associated with As enrichment in UG. As speciation indicated the prevalence of oxidized conditions. Saturation index of Fe oxides/hydroxides indicated the correlation between As and Fe. Abstract: The mechanisms controlling arsenic (As) enrichment and mobilization associated with human health risk assessment of groundwater in the Longdong Basin, located in the southern part of the Loess Plateau, China, have been yet unexplained. This uncertainty is partly attributed to a poor understanding of groundwater arsenic management. To address this problem, this study investigated the occurrence and spatial distribution of As in unconfined groundwater (UG) and confined groundwater (CG) in the study area, integrated Self-Organizing Maps (SOM) and geochemical modeling to elucidate the mechanisms controlling As release and mobilization in groundwater, and conducted a health risk assessment of groundwater As. The results showed that 13.6% of UG samples ( n = 66) and 22.4% of CG samples ( n = 98) exceeded the WHO guideline limit of As (10 μg/L). The detailed hydrogeochemical studies showed that As-enrichment groundwater is dominated by Cl-Na type, and Gaillardet diagram indicated that evaporites weathering may contribute to As mobilization in CG. The SOM analysis combined with Spearman's correlation coefficient quantified the negative correlation between As and redox potential, dissolved oxygen, SO4 2−, NO3 −, and the positive correlation between As and HCO3 −, Mn in UG. In CG, As is positively correlated to pH and negatively to electrical conductivity, SO4 2−, Fe and Mn. The saturation indices of the mineral phases indicates an insignificant relationship between As and Fe. We conclude that under oxidizing conditions, evaporative controls and the desorption of Fe-oxides under alkaline and high salinity conditions are the dominant mechanisms controlling As release and mobilization in groundwater. In addition, exposure to groundwater As through drinking water posed potential risk of carcinogenic and non-carcinogenic effects on children and adults. This study contributes to groundwater As management and sustainable safe groundwater supply. Graphical abstract: Image, graphical abstract